FACTORS AFFECTING CAN THO RESIDENTS’ INTENTION TO VISIT DALAT IN THE COVID-19 ERA - Cong Thanh Dinh; Le Hong Nhung Pham; Thu Ngan Le (Tạp chí Khoa học Đại học Đà Lạt, 2022)
The paper examines the factors affecting the intentions of Can Tho residents to travel to Dalat as the COVID-19 pandemic is gradually brought under control. The data were collected from a survey of 213 Can Tho residents and analyzed with Cronbach’s alpha, exploratory factor analysis, confirmatory factor analysis, and structural equation modeling. The results show that the intentions of Can Tho residents to travel to Dalat depend on four factors: (1) attitude toward Dalat tourism, (2) subjective norms, (3) perceived behavioral controls, and (4) perceived health risk. In particular, the attitudinal factor significantly influences Dalat travel intentions. Based on the research results, the article proposes four recommendations for managers, corresponding to the four influencing factors, to increase the intentions of Can Tho residents to travel to Dalat in the COVID-19 era.